2017
DOI: 10.1259/bjr.20160871
|View full text |Cite
|
Sign up to set email alerts
|

The impact of simulated motion blur on lesion detection performance in full-field digital mammography

Abstract: Objective: Motion blur is a known phenomenon in full-field digital mammography, but the impact on lesion detection is unknown. This is the first study to investigate detection performance with varying magnitudes of simulated motion blur.Method: Seven observers (15±5 years' reporting experience) evaluated 248 cases (62 containing malignant masses, 62 containing malignant microcalcifications and 124 normal cases) for three conditions: no blurring (0 mm) and two magnitudes of simulated blurring (0.7 mm and 1.5 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 22 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…Moreover, Ma et al investigated the minimum amount of simulated motion blur detected visually by radiologists, which was determined to be 0.7 mm. The realism of their mathematical blur simulation model was validated by an observer study and was found to be comparable to real blur in mammograms.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Moreover, Ma et al investigated the minimum amount of simulated motion blur detected visually by radiologists, which was determined to be 0.7 mm. The realism of their mathematical blur simulation model was validated by an observer study and was found to be comparable to real blur in mammograms.…”
Section: Introductionmentioning
confidence: 85%
“…Although limited work has been done to quantify the effects of motion blur on radiologists' performance, there is evidence that motion blur might not be detected visually by a human observer and it can negatively affect lesion detection performance. 1,3,7 As of this date, no other has study investigated the ability of machine-learning classifiers and BM operators to detect motion blur in mammograms; this work has. When distinguishing blurry from unblurry mammograms, the average classification accuracies were above 85% and 92% for the INbreast and DDSM mammographic databases, respectively, when using Ensemble Bagged Trees, fine Gaussian SVM, and weighted KNN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations